Transiting through the antiquities market: a social network Analysis of auctions - Fabiani, Michelle D. (Crime and art, 2021)
The antiquities market repeatedly raises concerns about money laundering, forgeries, and illicit trafficking. Auction houses’ and dealers’ roles in these activities are heavily studied, but there has been little research looking at connections between these market participants. We show the potential for social network analysis illuminate new aspects of the art market. In this case study, we track 30,000 individual items based on catalogued provenance information indicating their prior transit through various auction houses and dealers. The network inferred from these data allows us to address basic questions about the structure of the antiquities market, such as the rate of transit for items in the market, the pathways taken by items between auction houses, and the relationship between sale outcomes and re-appearance at auction. There are two types of objects that reappear at auction: those that failed to sell and are re-auctioned very quickly, and those that are held by a collector for about a decade before returning to auction. We also show that private dealers play a relatively important role in “vetting” certain objects, lending them legitimacy. Finally, we discuss additional uses of social network analysis and possible data sources for future art market researchers.